Are we still afraid of influenza during the Sars-Cov2 pandemic? - epidemiological analysis of influenza morbidity and vaccination in the 2019/2020 season - Ruszel, Kinga; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Influenza is an infectious respiratory disease that is caused by influenza A and B viruses in humans. Pandemic outbreaks mainly involve type A virus of zoonotic origin. The severity of the pandemic flu depends on many factors, including the virulence of the pandemic virus strain and the level of pre-existing immunity. Symptoms associated with influenza virus infection differ from mild respiratory disease limited to the upper respiratory tract and are characterized by fever, sore throat, runny nose, cough, headache, muscle pain and fatigue, as well as severe and in some cases fatal pneumonia due to influenza virus or secondary bacterial infection of the lower respiratory tract. The influenza virus is quite often subject to modifications, which makes it necessary to formulate an influenza vaccine every year to match the circulating strains. These vaccines are not mandatory and, despite the broadly understood promotion among the public, they are not widely purchased. In addition, the vaccine’s effectiveness is quite low in the case of an antigenic mismatch between the vaccine and the circulating strain of the virus, which causes a still high level of illness during the year. In the 2019/2020 season, a significant decrease in the number of influenza cases was observed in Poland and in the world. In this work, we will take a closer look at the numerical values of people with influenza and discuss the possible causes of this decline. Did the Covid-19 pandemic favorably affect the incidence of another virus, such as the influenza virus, and cause its decline, or did it just overshadow the real numbers, put society to sleep, and diverted their attention?